Scroll, Stream, and Shop: The Effect of Live Streaming and Flash Sales on Impulse Buying Through E-WOM Among Shopee Generation Z Users in Surabaya - Ayuwangi, Bunga; Mujanah, Siti; Fianto, Achmad Yanu Alif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the influence of Flash Sale and Live Streaming on Impulse Buying with Electronic Word of Mouth (E-WOM) as a mediating variable among Shopee Generation Z users in Surabaya. Based on the Stimulus–Organism–Response (SOR) theory, data from 120 respondents were analyzed using PLS-SEM through SmartPLS 4.0. The results showed that Live Streaming had a positive and significant influence on Impulse Buying, while Flash Sale had no direct influence. Both Flash Sale and Live Streaming significantly influenced E-WOM, which in turn had a strong influence on Impulse Buying. E-WOM also acted as a mediator in the relationship between Flash Sale and Live Streaming on Impulse Buying. These findings strengthen the application of SOR theory in the context of young digital consumer behavior, highlighting the importance of trust-based interactive promotions to encourage impulsive buying.